The existence of karabhat symbolic communication in Tanean Lanjhang community in Madurese society - Sudahri, Sudahri; Ida, Rachmah (Faculty of Communications Science, Dr. Soetomo University, 2020)
Tanean Lanjhang (the long yard) is a large yard with traditional Madurese houses built in a row and facing each other. ‘Tanean’ means the distance between one house and another. Meanwhile, ‘Lanjhang’ is the area of the yard that extends along the Tanean. The group that inhabits the Tanean Lanjhang is a genealogical group from one lineage, usually from the maternal (matrilineal) line. These social phenomena happened in Sanatengah Village, Pasean District, Pamekasan Regency. The current research used descriptive qualitative methodology and studied the people of Sanatengah Village, Pasean Subdistrict, Pamekasan Regency and all its community components. The results of this study indicated that the Tanean Lanjhang community is a social order that maintains the influence of relatives in life. Communication between relatives exists because of the role of Pangaseppo, or the eldest person of the family; Oreng Toah (parents), or mother and father; and Taretan, or siblings. Those were the three relatives who have the highest position in Madurese society and must be obeyed by every household members. In maintaining kinship, marriage is also arranged within close relatives, such as between cousins, uncles, and nieces. This study concluded that the Tanean Lanjhang upholds the values of kinship. Furthermore, kinship is not only built based on traditional houses but also the tradition of marriage between close relatives.